Integrating Evidence-Based Practice into Nursing School Curricula: Review of Educational Strategies for Enhancing Competencies in Evidence-Based Care Delivery - Alotabi, Abdulkareema Jahaz Dgaleb; Alotaibi, Malik Begad Mefries; Khawaji, Ghaziyh Abdu Abdu; Alhulayyil, Alanoud Abduallh; Alanezi, Seham Abdalmohsen; Aldossary, Guzail Ibrahim; Mahboob, Fatima Mohmmad Hassan; Albahli, Mohammed Ali; Alwrafi , Abdulaziz; Asiri, Hashedh Ali; Alshahrani , Faleh Mubarak; Almotairi, Naif Ali Rabaia; et al. (Journal of Ecohumanism, 2024)
Background: The integration of evidence-based practice (EBP) into nursing curricula is essential for enhancing the quality of patient care and ensuring patient safety. Despite its recognized importance, the implementation of EBP remains inconsistent among healthcare professionals due to various barriers, including insufficient training and lack of resources. Methods: This review systematically evaluates the literature on educational interventions aimed at enhancing EBP competencies among nursing students and practicing nurses. A comprehensive search was conducted across multiple databases, including Medline, PubMed, and CINAHL, to identify studies published up to 2023. The review focused on assessing the effectiveness of various pedagogical approaches, such as mentorship, online education, and hands-on training, in fostering EBP skills. Results: The findings indicate that structured educational programs significantly improve nurses' understanding and application of EBP. Mentorship and collaborative learning environments emerged as particularly effective strategies, leading to increased confidence and competence in applying EBP principles. However, a notable gap remains in the practical implementation of EBP in clinical settings, highlighting the need for ongoing support and resources. Conclusion: Integrating effective EBP educational interventions into nursing school curricula is crucial for preparing future healthcare professionals to deliver high-quality, patient-centered care. Addressing the identified barriers through targeted educational strategies can enhance EBP adoption in clinical practice. Future research should focus on the long-term impacts of these interventions and explore innovative approaches to sustain EBP in healthcare settings